(untitled) (Fiep Bulletin - online, 2011)
AIDS has increasingly come hurdling and borders, developing unpredictably between individuals from all continents and in full reproductive activity, at a high rate among young women. Also, has undergone rapid and significant epidemiological changes the test of time. It is in this context that this work was carried out in order to describe the epidemiological and clinical characteristics of patients with HIV/AIDS health care in a reference to the treatment of infectious diseases in Natal/RN, Brazil. This is an epidemiological study, descriptive, quantitative, and developed at the Giselda Trigueiro Hospital, a reference in the treatment of AIDS, located in the city of Natal/RN, Brazil. The target population consisted of all 313 patients with HIV treated in the period August 2007 to July 2008, in the days of the outpatient consultations. As an instrument of data collection used a form of interview with structured questions, validated through a pilot study. Identified that 180 (57, 5%) were men and 133 (42, 5%) women, being the predominant age group of 31 to 40, 122 (39, 0%). They also supplied the city of Natal, 178 (56, 9%) and in the state of RN, 135 (43, 1%). The monthly family income was observed that 111 (35, 5%) had income as less than minimum wage. The proportion of individuals with elementary school was 165 (52, 7%). The most prevalent form of contamination of the participants, according to those interviewed, it was through heterosexual transmission 187 (59, 7%). The input from users for monitoring the service, 79, 2% already had one sign or symptom indicative Immunodeficiency. In this study, the profile of those interviewed following the trend of other Brazilian cities.